2020
DOI: 10.3389/fevo.2019.00457
|View full text |Cite
|
Sign up to set email alerts
|

A Total Evidence Phylogenetic Analysis of Pinniped Phylogeny and the Possibility of Parallel Evolution Within a Monophyletic Framework

Abstract: In the present study, a series of phylogenetic analyses of morphological, molecular, and combined morphological-molecular datasets were conducted to investigate the relationships of 23 extant and 44 fossil caniforme genera, in order to test the phylogenetic position of putative stem pinniped Puijila within a comprehensive evolutionary framework. With Canis as an outgroup, a Bayesian Inference analysis employing tip-dating of a combined molecular-morphological (i.e., Total Evidence) dataset recovered a topology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 127 publications
3
37
2
Order By: Relevance
“…In practice, however, most of the recent TED studies included one to a handful of outgroup taxa, which are thus severely underrepresented compared to the ingroup, both in terms of morphological characters and fossils ( Ronquist et al 2012a ; Arcila et al 2015 ; Dornburg et al 2015 ; Close et al 2016 ; Lee 2016 ; Kittel et al 2016 ; Herrera and Davalos 2016 ; Bannikov et al 2017 ; Wang et al 2018 ; Paterson et al 2020 ). The reasons for including these outgroups, despite their potentially negative effects, is seldom reported in these studies and might vary between authors.…”
mentioning
confidence: 99%
“…In practice, however, most of the recent TED studies included one to a handful of outgroup taxa, which are thus severely underrepresented compared to the ingroup, both in terms of morphological characters and fossils ( Ronquist et al 2012a ; Arcila et al 2015 ; Dornburg et al 2015 ; Close et al 2016 ; Lee 2016 ; Kittel et al 2016 ; Herrera and Davalos 2016 ; Bannikov et al 2017 ; Wang et al 2018 ; Paterson et al 2020 ). The reasons for including these outgroups, despite their potentially negative effects, is seldom reported in these studies and might vary between authors.…”
mentioning
confidence: 99%
“…The sea otter is the only extant marine mammal that employs a crushing biting strategy. In the past, the durophagous niche was occupied by the phocid Hadrokirus (Amson and de Muizon, 2014) and aquatic bear/pinnipedimorph Kolponomos (Tseng et al, 2016;Paterson et al, 2020). Marine mammals that employ a crushing biting strategy FIGURE 2.…”
Section: Anatomy Of Feedingmentioning
confidence: 99%
“…Stem pinnipedimorphs are mostly reconstructed as having had an ancestral coastal marine habitat as is characteristic of most extant taxa (Appendix 5). Since the fossil Puijila is now identified as a pinnipedimorph (Paterson et al, 2020) a lacustrine ancestral habitat is also indicated. The stem otariid Eotaria is reconstructed as having had a pelagic marine habitat.…”
Section: Ancestral Reconstructions Of Feeding Strategies and Trophic mentioning
confidence: 99%
“…However, loss of these receptors occurred independently in the ancestors of the reciprocally monophyletic Phocidae (seals) and Otaroidea (Otariidae [sea lions, fur seals] + Odobenidae [walruses]) rather than in the common ancestor of Pinnipedia [100]. Numerous morphological features related to raptorial feeding and hydrodynamic locomotion also appear to have evolved independently in the three extant families of Pinnipedia [101]. In Cetacea, multiple cranial and postcranial specializations for an aquatic lifestyle (e.g., shortened humerus, loss of radial tuberosity, reduction/loss of hindlimbs, posterior migration of the blowhole, cranial 'telescoping') evolved convergently in odontocetes and mysticetes [1,102,103].…”
Section: Anthracotherium Siamotherium) Appear To Have Been Terrestrimentioning
confidence: 99%